Synthesis, in vitro antiproliferative activity, and kinase inhibitory effects of pyrazole-containing diarylureas and diarylamides - El-Gamal, Mohammed I.; Park, Byung-Jun; Oh, Chang-Hyun (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2018)
Twenty pyrazole-containing diarylureas and diarylamides were designed and synthesized. They were tested for in vitro antiproliferative activity over a 58-cancer cell line panel at the NCI, USA. The diarylurea derivatives lb-e and lg exerted the strongest antiproliferative activity. Among them, compound le possessing 3,5-bis(trifluoromethyl)phenyl terminal ring and 3'-methoxy-5'-chlorophenyl ring attached to the central pyrazole ring was the most potent. Its IC50 values were in sub-micromolar range against most of the tested cell lines. It showed superior potency than sorafenib, a reference diarylurea drug, over all the tested cell lines. It was also extremely selective towards cancer cells than non-cancerous cells (IC50 against RAW 264.7 macrophages was higher than 100 mu M). At molecular level, compound le selectively inhibited V600E mutated B-RAF kinase (IC50 = 0.39 mu M). It also stimulated caspase 3/7 enzymes in RPMI-8226 leukemia cells (2.79 fold increase at 10 mu M concentration, EC50 = 1.52 mu M). So compound le may kill cancer cells through induction of apoptosis. This promising candidate can be considered further for development of new efficient anticancer agents. (C) 2018 Elsevier Masson SAS. All rights reserved.
Keywords: MELANOMA-CELL LINE; SPECTRUM ANTICANCER AGENTS; 1,3,4-TRIARYLPYRAZOLE SCAFFOLD; PART 2; DERIVATIVES; DESIGN; CANCER; TRIARYLPYRAZOLES; SERIES